Anthropometric comparison of three-year-old Nigerian child and crash dummies - Rafukka, Ibrahim Abdullahi; Sahari, Barkawi; Abdul Aziz, Nuraini; Arumugam, Manohar (Scientific Research Publishing, 2016)
In this work, anthropometric data measured from three-year-old Nigerian child were compared with United States anthropometric database collected by Snyder, 1977 which formed the basis of US anthropometry used today. Further comparison was also carried out with the dimensions of crash dummies: Hybrid III three-year-old (HIII 3YO) and Q3s dummies in order to determine the validity of using such crash dummies for safety evaluation of cars and child restraint systems (CRS) used for Nigerian children. Anthropometric survey was performed on 30 Nigerian children aged 2.5 to 3.5 years old. Twenty three standard measurements were taken from each child including the weight, height and circumferences etc. Various percentiles mean and standard deviation values were obtained and compared with international database. As observed, the dimensions of three-year-old Nigerian child appeared to be about 25% lower than US data reported by Snyder. Significant difference was also found between the dimensions of three-year-old Nigerian child and crash dummies. This study provides the external dimensions of 3-year-old Nigerian child that could be used for crash dummy and CRS design.